Cyclical and structural variation in resource allocation: Evidence for Europe - Eric Jan Bartelsman; Paloma López-García; Giorgio Presidente (European Central Bank (ECB), 2018)
This paper uses cross-country micro-aggregated data on firm dynamics and productivity from the ECB CompNet database to provide empirical evidence on factor reallocation in the European Union (EU). The analysis finds that reallocation is towards more productive firms although the magnitude varies across countries and over time. Variation in reallocation is related to structural differences in firm size distribution across countries as well as to variation in labor and product market institutions. Productivity-enhancing reallocation generally rises in downturns but, similar to findings for the US, it did not pick up in the Great Recession. The sharp drop in exports and tightness in credit markets are seen to provide a partial explanation for this lack of a silver lining.
Keywords: E24; E32; J63; O4; 330; Great Recession; Factor Reallocation